A LITERATURE REVIEW: FACILITATING SPIRITUALITY IN CHILDREN WITH INTELLECTUAL DISABILITIES - Jessica Ariela (Nursing Current: Jurnal Keperawatan, 2018)
Children with intellectual disabilities are often treated as having less value. Increased awareness of holistic personhood, however, brought questions to the need to facilitate spirituality in these children, besides facilitating the development of other aspects. Previous studies argued that children with intellectual disabilities have potentials to develop spiritually despite the very few studies addressing the spirituality in children with intellectual disabilities. This literature review, then, aims to explore methods and interventions to facilitate spirituality in children with intellectual disabilities, through a comprehensive analysis and synthesis of the themes drawn from existing literatures and research studies. After the analysis and synthesis process, four themes emerged for intervention methods to facilitate spiritual development in intellectually challenged children, which are: narratives (from Scripture and personal narratives); symbols, liturgies, and rituals; arts and kinesthetic learning; and community, group, and social support. Further research studies, especially using quantitative methods, are encouraged to be conducted in the future in order to assess the efficacy of each method of interventions.